Difference in performance assessments conducted indoors and outdoors in professional cyclists - Lipski, E. S.; Spindler, D. J.; Hesselink, M. K. C.; Myers, T. D.; Sanders, D. (International Journal of Sports Physiology and Performance, 2022)
Purpose: The purpose of this study was to assess the relationship between typical performance tests among elite and professional cyclists when conducted indoors and outdoors. Methods: Fourteen male cyclists of either UCI (Union Cycliste Internationale) Continental or UCI World Tour level (mean [SD] age 20.9 [2.8] y, mass 68.13 [7.25] kg) were recruited to participate in 4 test sessions (2 indoors and 2 outdoors) within a 14-day period, consisting of maximum mean power testing for durations of 60, 180, 300, and 840 seconds. Results: Across all maximum mean power test durations, the trimmed mean power was higher outdoors compared with indoor testing (P < .05). Critical power was higher outdoors compared with indoors (+19 W, P = .005), while no difference was observed for the work capacity above critical power. Self-selected cadence was 6 rpm higher indoors versus outdoors for test durations of 60 (P = .038) and 300 seconds (P = .002). Conclusions: These findings suggest that maximal power testing in indoor and outdoor settings cannot be used interchangeably. Furthermore, there was substantial individual variation in the difference between indoor and outdoor maximum mean powers across all time durations, further highlighting the difficulty of translating results from indoor testing to outdoor on an individual level in elite populations.